The correlation between strength and range of motion of the neck muscles and opium smoking in Iran - Massah, Omid; Arab, Amir Masoud; Farhoudian, Ali; Noroozi, Mehdi; Hashemirad, Fahimeh (Frontiers in Psychiatry, 2023)
Objectives Opium smoking is commonly practiced via traditional and novel routes in Iran. Both smoking methods are practiced in a non-ergonomic position. According to previous studies and our hypothesis, it can be potentially harmful to the cervical spine. Thus, the present study aimed to investigate the relationship between opium smoking and neck range of motion and neck muscle strength. Methods In this cross-sectional and correlational study, the range of motion and strength of the neck muscles of 120 men with drug use disorder were measured by a CROM goniometer and a hand-held dynamometer. Other data gathering was performed using a demographic questionnaire, the Maudsley Addiction Profile, and the Persian version of Leeds Dependence Questionnaire. The obtained data were analyzed by Shapiro–Wilks test, Pearson’s correlation coefficient and stepwise linear regression. Results There was no significant correlation between the age of drug use onset and range of motion and muscle strength of the neck; however, the daily duration of opium smoking and the number of years of opium smoking were inversely and significantly correlated with the range of motion and muscle strength of the neck in some directions. Daily opium smoking time for decreasing in neck range of motion and total duration of opium smoking for reduction of neck muscles strength are stronger predictor variables. Conclusion Opium smoking by traditional routes causes non-ergonomic positions and has a moderate significant correlation with reduced range of motion and neck muscle strength, in Iran. Highlights – The harm of drug use disorder is not only AIDS and hepatitis, and harm reduction programs should go beyond the prevention of AIDS and hepatitis. According to more than 90% of smoking use of drug compared to other methods (oral and injectable, etc.) musculoskeletal disorders caused by the smoking use of drugs, have a greater cost burden in reducing the quality of life and the need for rehabilitation. – Drug abuse treatment and harm reduction programs should focus more seriously on replacing smoking use of drugs with oral medications assisted treatment. – Although in Iran and some countries in the region, a large number of people smoke opium for many years and sometimes all their lives, daily in a completely non-ergonomic position, but studying the deformation of the posture and musculoskeletal disorders related to the body position in them, is not a scientific concern and neither physical therapy researchers have paid attention to it nor addiction researchers. – Neck muscles strength and range of motion in opium addicts are correlated to the number of years of opium smoking and daily minutes of opium smoking, but not to its oral use. – There is no significant correlation between the onset age of continues and permanent opium smoking and substance dependence severity with neck range of motion and muscles strength. – People with drug use disorder (especially smoking users) as a large group of vulnerable people, should be the target population of musculoskeletal disorders researchers and addiction harm reduction researchers, and more experimental, comparative, cohort, etc. researches should be designed and implemented for them.